Constable & Toop - Jones, Gareth P. (Amulet Books, 2013)
In Victorian London, an undertaker's son who can see ghosts and is haunted by their constant demands for attention must decide whether to help when a horrible disease imprisons ghosts into empty houses in the world of the living.